A reliable procedure to obtain environmentally relevant nanoplastic proxies. Issue 11 (6th October 2021) - Blancho, Florent; Davranche, Mélanie; Fumagalli, Francesco; Ceccone, Giacomo; Gigault, Julien
Abstract : More environmentally relevant nanoplastic models are urgently needed. Abstract : More environmentally relevant nanoplastic models are urgently needed. Models of environmental plastics are used to develop analytical methods to get an accurate picture of how nanoplastics behave in natural systems, and to generate data on nanoplastics' environmental fate and impact on living organisms. Despite the recent progress in developing models to mimic nanoplastics, the models that are available do not yet show enough diversity to represent the wide heterogeneity in the physical and chemical properties of environmental nanoplastics. In this paper, we report on the strategy we developed to obtain environmentally relevant nanoplastics by mechanical abrasion and sonication of weathered plastics collected from the natural environment (on the beach, and floating in the water). An organic matter degradation protocol was devised to eliminate any potential organic residues that were initially present on the collected plastic samples. The final nanoplastic suspension contains an average of 400 mg carbon L −1, allowing the surface properties to be characterized by XPS, BET analysis, and potentiometric titration. The size distribution of nanoplastics ranges from 200 to 500 nm, with a heterogenous shape and composition (polyethylene or polypropylene) similar to the nanoplastics observed in marine, coastline, and soil systems.